Ultrasonographic review of pediatric breast masses among Nigerian children in a tertiary hospital - Sefiya Adebanke Olarinoye-Akorede; Phillip Oluleke Ibinaiye; Lawal B Suleiman (Wolters Kluwer Medknow Publications, 2020)
X Background: Breast masses occur infrequently in children and adolescents. Most of these masses have proved that benign and conservative approach is the management of choice. Consequently, imaging has become crucial. The knowledge of the ultrasonographic features of childhood and adolescent breast masses is needed for age appropriate medical care. Aim: The aim of this study was to describe and document the ultrasonographic spectrum of breast masses in children and adolescents (0-19) years seen in the Ahmadu Bello University teaching hospital, Zaria. Materials and Methods: A 2-year retrospective review of breast sonograms of 25 consecutively presenting children and adolescents (3 males and 22 females) who had palpable breast masses. Ultrasound scans were performed with a Mindray Machine DC-8 using the linear transducer at 7.5-12 MHz transducer frequency. Histopathological confirmation of the solid masses was also obtained. The statistical analysis of the data collected was done using the SPSS software version 20 (SPSS Inc., Chicago, IL, USA). Results: The patients were between 40 days and 19 years old (mean 14.8 years and standard deviation 4.1). The ultrasonographic findings were those of infections, benign tumoral lesions and pubertal endocrine changes. Overall, fibroadenoma was the most common mass, seen in 14 (56%) of the patients. Other findings were simple cysts, non-puerperal and puerperal mastitis, juvenile papillomatosis and normal glandular pubertal breast tissue. The three male patients had gynaecomstia, pseudogynaecomastia and cystic lymphangioma of the chest wall presenting as unilateral breast masses, respectively. There was no malignancy recorded in any of the patients. Conclusion: Ultrasonographically, benign masses predominate which is concordant with surgical findings. Familiarity with these features would obviate the need for unnecessary invasive procedures which should be reserved for only deserving cases.